Delivery of empty wagons: Choice of the proper contract design - А.А. Ananyeva (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is devoted to the choice of a more suitable kind of legal contract design for the regulation of relations emerging in the delivery of empty wagons that do not belong to the carrier. The relevance of the study is determined by the fact that, in connection with the reform carried out in railway transport, the rolling stock was separated from the carrier, and is currently provided by third parties. Despite this fact, the railway legislation does not offer the proper contractual arrangements. The following methods have been used: empirical methods of comparison, description, interpretation; theoretical methods of formal and dialectic logic. Specific scientific methods have been used: legal-dogmatic method and interpretation of legal norms. Three possible variants have been analyzed in detail. According to the first variant, these relations are covered by the contract of carriage of goods, and the empty wagons are considered as a special kind of cargo. In the second variant, the empty wagon belonging to a person other than the carrier is a vehicle, and then it becomes relevant whether the legal design of the contract of haulage is possible. The subject and object of the contract and the subject composition have been considered. The question has been examined whether the empty wagon can be considered a vehicle. The paper contains a number of reasons proving that the recognition of the wagon by means of a vehicle excludes the possibility of identifying it with a cargo that delimits the subject composition and content of the contract for the carriage of goods and the contractual design applicable to the carriage of empty wagons. Based on the results of the study, it has been concluded that the design of the contract of haulage should be used for the foregoing purposes.